1988
DOI: 10.1136/vr.122.13.302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison by experimental infections in cattle of a Dictyocaulus species occurring naturally in red deer and a dictyocaulus of bovine origin

Abstract: Dictyocaulus species larvae were obtained from young red deer which had become infected on pastures considered to be carrying the Dictyocaulus species indigenous to the red deer of Scotland. These larvae were cultured to third stage and transmitted to five bovine calves. Five other bovine calves were infected with third stage Dictyocaulus viviparus larvae of bovine origin. Microscopic appearances of both groups of larvae were indistinguishable and their lengths were similar. Results indicated that the Dictyoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…There are a variety of parasites which cause infections of the lower respiratory tract. For example, the lungworm Dictyocaulus viviparus is pathogenic in cattle and deer although the immature stages of Elaphostrongylus cervi, too, can damage the lungs (Munro and Hunter, 1983;Corrigall et al, 1988). In the present material, only different stages of D. eckerti were identified in naturally infected reindeer.…”
Section: Discussionmentioning
confidence: 53%
“…There are a variety of parasites which cause infections of the lower respiratory tract. For example, the lungworm Dictyocaulus viviparus is pathogenic in cattle and deer although the immature stages of Elaphostrongylus cervi, too, can damage the lungs (Munro and Hunter, 1983;Corrigall et al, 1988). In the present material, only different stages of D. eckerti were identified in naturally infected reindeer.…”
Section: Discussionmentioning
confidence: 53%
“…Strain differences of D. viviparus originating from wild cervids or domestic livestock may also account for differences in pathogenicity. Using experimentally infected cattle, Corrigall et al (1988) demonstrated that cattle infected with the red deer strain of D. viviparus had milder infections than cattle infected with the cattle strain.…”
Section: Discussionmentioning
confidence: 99%
“…Our results which indicated limited pathogenicity following administration of 2,000 or 3,000 larvae in the seven elk agree with the one elk inoculated with 24,000 larvae of bovine origin (Presidente et al, 1972), and with reports regarding experimental infections in red deer. Studies in three 6-mo-old red deer inoculated with 500 D. viviparus larvae per kg of body weight (no red deer weights given) for 17 consecutive days indicated that infected red deer had reduced food intakes and weight gains compared to one noninfected red deer, but that the infection was mild (Corrigall et al, 1982). The pathology in the infected red deer was different from the pathology observed in cattle in that alveolar epithelialisation was limited and hyaline membrane formation and interstitial emphysema were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments prompted Enigk and Hildebrandt (1965) to conclude that D. viviparus infection was more adapted to deer than cattle because infections persisted longer in deer than in bovines and were less pathogenic. However, when Corrigall et al (1988) successfully infected bovine calves with a red deer strain of D. viviparus, pathogenicity was greatly reduced. In a reciprocal experiment, bovine strain D. viviparus caused more pathology than red deer strain D. viviparus in red deer fawns.…”
mentioning
confidence: 99%
“…Concern about wild ruminants contaminating pastures has led to a variety of cross-transmission studies. Corrigall et al (1988), felt that deer strain D. viviparus was less pathogenic than cattle strain Dictyocaulus, and posed no serious threat to cattle grazing pastures occupied previously or simultaneously with red deer. In North America, studies involving cross-transmission with D. viviparus isolated from elk (Presidente et al, 1972), moose (Gupta and Gibbs, 1971), and black-tailed deer (Presidente and Knapp, 1973) indicated that these strains do not mature in cattle.…”
mentioning
confidence: 99%